Drought–heatwave nexus in Brazil and related impacts on health and fires: A comprehensive review. Issue 1 (2nd September 2022) - Libonati, Renata; Geirinhas, João L.; Silva, Patrícia S.; Monteiro dos Santos, Djacinto; Rodrigues, Julia A.; Russo, Ana; Peres, Leonardo F.; Narcizo, Luiza; Gomes, Monique E. R.; Rodrigues, Andreza P.; DaCamara, Carlos C.; Pereira, José Miguel C.; et al.
Abstract: Climate change is drastically altering the frequency, duration, and severity of compound drought‐heatwave (CDHW) episodes, which present a new challenge in environmental and socioeconomic sectors. These threats are of particular importance in low‐income regions with growing populations, fragile infrastructure, and threatened ecosystems. This review synthesizes emerging progress in the understanding of CDHW patterns in Brazil while providing insights about the impacts on fire occurrence and public health. Evidence is mounting that heatwaves are becoming increasingly linked with droughts in northeastern and southeastern Brazil, the Amazonia, and the Pantanal. In those regions, recent studies have begun to build a better understanding of the physical mechanisms behind CDHW events, such as the soil moisture–atmosphere coupling, promoted by exceptional atmospheric blocking conditions. Results hint at a synergy between CDHW events and high fire activity in the country over the last decades, with the most recent example being the catastrophic 2020 fires in the Pantanal. Moreover, we show that HWs were responsible for increasing mortality and preterm births during record‐breaking droughts in southeastern Brazil. This work paves the way for a more in‐depth understanding on CDHW events and their impacts, which is crucial to enhance the adaptive capacity of different Brazilian sectors. Abstract : Climate change is drastically altering the frequency, duration and severity of compound drought‐heatwave (CDHW) episodes, which present a new challenge in environmental and socio‐economic sectors. These threats are of particular importance in low‐income regions with growing populations, fragile infrastructure, and threatened ecosystems. This review synthesizes emerging progress in the understanding of CDHW patterns in Brazil, while providing insights about the impacts on fire occurrence and public health.